2022
DOI: 10.3389/fpls.2022.878289
|View full text |Cite
|
Sign up to set email alerts
|

Micrographic View of Graft Union Formation Between Watermelon Scion and Squash Rootstock

Abstract: Grafting has become a common practice for watermelon [Citrullus lanatus (Thunb.) Matsum & Nakai] production in many parts of the world, due to its efficacy against biotic and abiotic stressors. However, grafting success for watermelon is challenging in part due to the complex anatomy of the cucurbit vascular system. The survival of grafted transplants depends on compatibility between the scion and rootstock, which in turn depends on anatomical, physiological, and genetic variables. A better understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Vascular tissue reconnection was essential to grafting success, [ 39 ] and the different combinations of scion and rootstock took a different time to form vascular bundles fully. [ 40 ] In this study, we observed the vascular tissue connectivity of control and TRV‐ CmGH9B3 grafted plants (Figure 3) and found that the TRV‐ CmGH9B3 grafted plants were delayed by one day compared to the control grafted plants. The results suggested that silencing CmGH9B3 could significantly delay the cell adhesion time at the grafted interface of oriental melon scion and squash rootstock.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Vascular tissue reconnection was essential to grafting success, [ 39 ] and the different combinations of scion and rootstock took a different time to form vascular bundles fully. [ 40 ] In this study, we observed the vascular tissue connectivity of control and TRV‐ CmGH9B3 grafted plants (Figure 3) and found that the TRV‐ CmGH9B3 grafted plants were delayed by one day compared to the control grafted plants. The results suggested that silencing CmGH9B3 could significantly delay the cell adhesion time at the grafted interface of oriental melon scion and squash rootstock.…”
Section: Discussionmentioning
confidence: 73%
“…Vascular tissue reconnection was essential to grafting success, [39] and the different combinations of scion and rootstock took a different time to form vascular bundles fully. [40] In this study, we observed the vascular tissue connectivity and sucrose metabolism pathways were deeply explored. Some reports suggested that plant hormone signaling was essential for graft union healing.…”
Section: Discussionmentioning
confidence: 99%